Hubungan antara Supervisi Akademik dengan Kompetensi Profesional Guru Sekolah Dasar - Beatrix Hayudityas; Herry Sanoto (Universitas Cokroaminoto Palopo, 2021)
One of the competencies that a teacher must have is professional competence. This professional competency includes the ability of teachers in mastering learning materials, learning models, understanding learning concepts so that they can apply them in the learning process. This professional competency needs to be developed, therefore the principal has a way or effort in helping to improve the professional competence of teachers, namely by conducting academic supervision. This academic supervision aims to provide assistance, guidance, direction and assessment to teachers. This research aims to find out the relationship between academic supervision and professional competence of teachers. This research is an experimental research correlation with quantitative approach. The methods used in this study are statistical and descriptive methods. The data collection techniques used in this study are questionnaires and documentation studies. The sampels used in this study were 8 people, namely 1 principal and 3 teachers from Kanisius Harjosari Primary School and 1 principal and 3 teachers from Marsudirini 77 Salatiga Primary School. The results of this study showed that the correlation between academic supervision and professional competence amounted to 0,026 ehich means that there is a relationship or correlation with the correlation strength of 0,768 which belongs to the category is very strong and the relationship of academic supervision with professional competence is in the same direction.